Clinico-mycological assessment of pediatric dermatophytosis: experience of an eastern Indian tertiary hospital - Arya Bose; Abheek Sil; Loknath Ghoshal (Turkderm Turkish Archives of Dermatology and Venereology)
Background and Design: The ongoing rampage of dermatophytic infection continues to challenge dermatologists with its varied presentations, sparing no age group. Thus, this study was undertaken to assess the clinical, demographic, and microbiological aspects of childhood tinea infection. Materials and Methods: A descriptive, cross-sectional study was conducted in 200 consecutive pediatric patients (under 14 years of age) diagnosed with dermatophytosis between January 2019 and March 2020. All patients underwent detailed history, thorough clinical examination, microbiological confirmation with potassium hydroxide mount and fungal culture. Results: The majority of the study population (44.5%) belonged to the 3 ≤9 years age group with a mean age of 6.1 +- 3.3 years, with an overall male predominance. More than one-third of the patients (39%) belonged to the ‘low' socioeconomic stratum and lived in rural areas. Similar affliction among family members was recorded in 83.5%. Chronic and recurrent dermatophytosis was diagnosed in 9% of patients. The most common site involved was the trunk. Clinically, the most commonly diagnosed condition was tinea corporis (92%). More than half of the patients (53.5%) reported usage of prior topical steroid-laced creams. The most common fungus was Trichophyton mentagrophytes. Conclusion: A substantial pediatric population is afflicted by the ongoing scourge of superficial dermatophytosis. Results from our study corroborate with the studies done by Indian investigators on adult patients suffering from dermatophytosis. Multicentric collaboration with added molecular studies assessment is needed to address this growing concern in the pediatric age group.